What Makes Redundant Presentation of Multimedia Learning Difficult?. (2nd June 2015) - Soruç, Adem
Abstract: Research on multimedia learning and on reading comprehension has become ubiquitous over the last decades. Somewhat more specifically, redundancy principle of multimedia learning has been investigated a lot in many different, notably ESL, settings. Yet, much closer qualitative examinations are still needed. To this end, the present study aims to investigate firstly what kind of difficulties "EFL" students go through in redundant and non-redundant conditions and then how they feel about these presentations. Think-aloud protocols and interviews revealed a) split attention effect, b) the role of pictures with moving arrows and c) the importance of native/nonnative speaker speech. Implications are given and suggestions made for teachers and material developers at the end.